Fuzzy Fixed Point Results in F-Metric Spaces with Applications. (6th July 2020) - Alansari, Monairah; Mohammed, Shehu Shagari; Azam, Akbar
Abstract : In this paper, some concepts of F -metric spaces are used to study a few fuzzy fixed point theorems. Consequently, corresponding fixed point theorems of multivalued and single-valued mappings are discussed. Moreover, one of our obtained results is applied to establish some conditions for existence of solutions of fuzzy Cauchy problems. It is hoped that the established ideas in this work will awake new research directions in fuzzy fixed point theory and related hybrid models in the framework of F -metric spaces.